(untitled) (Malaysian Management Journal, 1995)
The value of plotting business performance data over time on a semi-logarithmic graph has been advocated, but in a somewhat offhand and intuitive way. While examples have been discussed, no mathematical justification has been. given. In this paper, we give such a justification in order to underscore, and perhaps acquaint the reader with this simple yet powerful graphics tool. We also discuss and illustrate an extension of the idea underlying this technique. These methods are particularly useful with spreadsheet packages which include graphics capabilities.